2008
DOI: 10.1063/1.2833057
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Constitutive Relationships in Energetic Materials: Petn and HMX

Abstract: and [111] directions up to compression ratio VAAQ = 0.70. Equilibrium properties, including lattice parameters and elastic constants, as well as hydrostatic EOS are in good agreement with available experimental data. The shear stresses of uniaxially compressed PETN-I and P-HMX have been evaluated and their behavior as a function of compression ratio has been used to make predictions of shock sensitivity of these EMs. A comparison of predicted sensitivities with available experimental data has also been perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Conroy et al [21][22][23] suggested that shear stress could be of importance in understanding the shock-induced anisotropy of EMs because it is usually considered to be the driving force behind plastic deformations in crystals and the source of mechano-chemical reactions behind the shock wave front. So they [21][22][23] performed a series of rst-principles density functional theory (DFT) calculations for uniaxially compressed PETN and HMX crystals to nd the relationship between shear stress and anisotropic sensitivity. The uniaxially compressed state of a crystal was used to mimic the state that the crystal experiences upon shock loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conroy et al [21][22][23] suggested that shear stress could be of importance in understanding the shock-induced anisotropy of EMs because it is usually considered to be the driving force behind plastic deformations in crystals and the source of mechano-chemical reactions behind the shock wave front. So they [21][22][23] performed a series of rst-principles density functional theory (DFT) calculations for uniaxially compressed PETN and HMX crystals to nd the relationship between shear stress and anisotropic sensitivity. The uniaxially compressed state of a crystal was used to mimic the state that the crystal experiences upon shock loading.…”
Section: Introductionmentioning
confidence: 99%
“…A correlation between shear stress and sensitivity for PETN and HMX was found: the magnitudes of the calculated shear stresses are greater for the more sensitive directions than for the less sensitive ones. [21][22][23] Recently, Zybin et al 24 developed a compress-shear reactive dynamics (CS-RD) computational strategy to examine the anisotropic shock sensitivity in PETN. The CS-RD method was developed to understand which aspects of the shock process are related to sensitivity by rst compressing the crystals, followed by shear deformation along various slip systems.…”
Section: Introductionmentioning
confidence: 99%
“…Conroy et al [22][23][24] suggested that shear stress could be of importance in understanding the shock-induced anisotropy of EMs because it is usually considered to be the driving force behind plastic deformations in crystals and the source of mechano-chemical reactions behind the shock wave front. Therefore, they [22][23][24] performed a series of first-principles density functional theory (DFT) calculations for uniaxially compressed PETN and HMX crystals to explore the relationship between shear stress and anisotropic sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Conroy et al [22][23][24] suggested that shear stress could be of importance in understanding the shock-induced anisotropy of EMs because it is usually considered to be the driving force behind plastic deformations in crystals and the source of mechano-chemical reactions behind the shock wave front. Therefore, they [22][23][24] performed a series of first-principles density functional theory (DFT) calculations for uniaxially compressed PETN and HMX crystals to explore the relationship between shear stress and anisotropic sensitivity. Upon the comparison of the simulated data with the experimental information, a correlation between shear stress and sensitivity was found: the magnitudes of the calculated shear stresses are greater for the more sensitive directions than for the less sensitive ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation